Pencegahan Gangguan Kesehatan Jiwa pada Remaja di Masa Pandemi Covid-19 dengan Perilaku “CERDIK CERIA” - Leliana Wuarlela; Lusa Rochmawati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: People are not ready to face the COVID-19 pandemic, physically or psychologically. Teenagers who often do activities outside the home such as going to school, playing, and others are affected. Behavioral factors (behavior causes) and factors outside of behavior (non-behavior causes) affect the health of a person or society. Efforts to overcome mental health in adolescents with